HUBUNGAN PARENTNING STYLE DAN TINGKAT PENGETAHUAN ORANG TUA TENTANG SEX EDUCATION PADA ANAK USIA DINI DENGAN PERILAKU PENCEGAHAN SEXUAL ABUSE DI TK NEGERI PEMBINA SUBANG - Dwi Diana Putri; Dini Rahmawati (Ensiklopedia Research and Community Service Review, 2026)
Sexual abuse in early childhood continues to rise and has become a serious issue, including in Subang Regency. Lack of parental knowledge about sex education and inappropriate parenting styles are contributing factors that increase this risk. Objective: This study aims to analyze the relationship between parenting style and parents’ level of knowledge about sex education for early childhood with sexual abuse prevention behavior at TK Negeri Pembina Subang. Methods: A quantitative research design with a cross-sectional approach was used. A total of 88 parents were selected through purposive sampling. The instruments included the Parenting Styles and Dimensions Questionnaire (PSDQ), a sex education knowledge questionnaire, and a sexual abuse prevention behavior questionnaire. Data were analyzed using Spearman Rank correlation tests. Results: Most parents applied a democratic parenting style (59.1%), had good knowledge of sex education (60.0%), and demonstrated good sexual abuse prevention behavior (72.7%). The Spearman Rank test indicated a significant relationship between parenting style and sexual abuse prevention behavior (r = 0.411; p 0.001), as well as between parental knowledge of sex education and prevention behavior (r = 0.363; p 0.001). Conclusion:There is a significant relationship between parenting style and parental knowledge about sex education and sexual abuse prevention behavior among parents of early childhood students at TK Negeri Pembina Subang. These findings highlight the importance of educating parents on sex education and implementing supportive parenting styles that encourage openness and child protection.     Keywords: Parenting Style, Parental Knowledge, Sex Education, Preventive Behavior, Sexual Abuse